A GENERALIZED DIRECT METHODS FOR THE LOADED NONLINEAR DEGASPERIS-PROCESI EQUATION - M.M.Xasanov; Sh.Sh.Omonov (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This paper is studied to finding the traveling wave solutions of the loaded nonlinear Degasperis-Procesi equation. By using the dynamical system theory the nonlinear Degasperis-Processi equation are studied .The bounded travelling wave solutions such as peakons are analytically described. The loaded Degasperis-Procesi equation is converted to the ordinary differential equation which are solved for all possible soliton solutions of Degasperis-Procesi equation. We construct exact travelling wave solution for loaded nonlinear Degasperis-Procesi equation,and the obtained solution agrees well with the previously known result.